Lymphocytic hypophysitis associated with Behcet's disease: A case report and review of the literature - Tao, Tingting; Zhang, Ziyi; Li, Hong (Neuro-endocrinology letters, 2018)
Lymphocytic hypophysitis (LH) is a rare inflammatory disorder involving the pituitary gland, often with other autoimmune diseases combined. The coexistence of LH and Behçet\'s disease (BD) is a rare combination and only one case was reported in the previous literatures. A 50-year-old man was admitted into Sir Run Run Shaw Hospital presented with frontal headache and fatigue which had lasted for four months. Endocrinological inspection indicated anterior pituitary dysfunction. Magnetic resonance imaging (MRI) revealed homogeneous pituitary enlargement and thickened pituitary stalk. Administration of glucocorticoids could effectively relieve headache and reduced pituitary mass volume. Oral aphthosis, skin lesions and positive pathergy tests were recognized later, which were characteristic features of BD. Although the diagnosis of BD is mainly dependent on clinical manifestations, PT is still a useful diagnostic tool 0f high specificityfor BD. And this male patient was diagnosed with both LH and BD afterwards. Then he was treated with cyclophosphamide and medium doses of methylprednisolone and remained in good conditions at the follow-up. LH and BD might share a common underlying autoimmune pathogenesis. The presentation of endocrinologic disturbances such as anterior pituitary dysfunction with typical features of skin lesions should prompt further investigation of possible comorbid autoimmune disease involving multiple organ systems. Early diagnosis and close monitoring are vitally important to ensure a stable endocrinologic status.